Deconvolution of B cell receptor repertoire in multiple sclerosis patients revealed a delay in tBreg maturation - Lomakin, Yakov A.; Zvyagin, Ivan V.; Ovchinnikova, Leyla A.; Kabilov, Marsel R.; Staroverov, Dmitriy B.; Mikelov, Artem; Tupikin, Alexey E.; Zakharova, Maria Y.; Bykova, Nadezda A.; Mukhina, Vera S.; Favorov, Alexander V.; Ivanova, Maria; et al. (Frontiers in Immunology, 2022)
Background: B lymphocytes play a pivotal regulatory role in development and suppression of the immune response. It was previously shown that deficiency in B regulatory cells (Bregs) or decrease in their anti-inflammatory activity may lead to various immunological disfunctions. However, the exact mechanism of Bregs functioning and development is only partially resolved. Particularly, almost noth-ing is known about the structure of their B cell receptor (BCR) repertoire in autoimmune disorders, including multiple sclerosis (MS), a severe neuroinflammatory disease with a still unknown etiology. Here, we elucidated the peculiarities of the B regulatory cells in MS. Methods: We performed a prospective study of transitional Breg (tBreg) subpopulation with CD19+ CD24highCD38high phenotype from MS patients and healthy donors (HD) by (i) measuring the portion of these cells during two opposite courses of relapsing-remitting MS – benign multiple sclerosis (BMS) and highly active multiple sclerosis (HAMS); (ii) analyzing BCR repertoire using high-throughput sequencing of B cells; and (iii) measuring the percentage of CD27+ cells among tBregs. Results: tBregs cells from patients with HAMS carry a heavy chain with lower amount of hypermu-tations in comparison with the healthy donors. The percentage of transitional CD24highCD38high B cells is increased, whereas the frequency of differentiated CD27+ cells among these transitional B cells is decreased in MS patients as compared to those in matched healthy individuals. Conclusions: Impaired maturation of regulatory B cells is associated with MS progression.